Gen Z Marriage: Loneliness as a Moderator of Partner Phubbing and Marital Satisfaction - Rinaldi, Martaria Rizky; Hardika , Jelang; Triastuti, Rinda (Fakultas Psikologi Universitas YARSI, 2025)
Generation Z, known as digital natives, is highly familiar with technology and social media, which can influence various aspects of life, including marital satisfaction. This study aimed to explore the role of loneliness as a moderator in the relationship between partner phubbing and marital satisfaction in Generation Z. A correlational quantitative approach with a cross-sectional design was employed in this research. The study involved 204 Generation Z participants aged 20-29 who had been married for 1-7 years. The research instruments included a partner phubbing scale, a marital satisfaction scale, and a loneliness scale. Data analysis was conducted using the moderation mediation module in Jamovi. The results indicated that both partner phubbing and loneliness were negatively related to marital satisfaction (Z = -2.633, p < .001; Z = -3.843, p < .001). This suggests that higher levels of phubbing experienced by partners are associated with lower reported marital satisfaction. Furthermore, greater loneliness was found to be linked to lower marital satisfaction in Generation Z. However, no moderating effect of loneliness was found in the relationship between partner phubbing and marital satisfaction (Z = 0.794, p = .427). This indicates that the impact of phubbing on marital satisfaction remains consistent for individuals with both low and high levels of loneliness. This study offers valuable insights for Generation Z couples on the impact of technology use on marital relationships, highlighting the importance of considering loneliness in maintaining relationship quality. Education on the mindful use of technology is crucial for achieving marital satisfaction among Generation Z.